Cloud data anonymous assured deletion approach based on blockchain - Shuangxing WANG; Jintang LUO; Lisha SHUAI; Jiamin ZHANG; Min ZHANG; Xiaolong YANG (Dianxin kexue)
The previous assured deletion schemes ignored that the privacy is threated by the relevance between data and user identity, exposing user behavior to the cloud service provider or attackers.Aiming at the above problems, an assured deletion approach based on blockchain was proposed.The improved linkable ring signature scheme was adopted to make user achieve anonymous assured deletion by setting specific link symbol in the signature.Moreover, the blockchain technology was leveraged to guarantee the nonrepudiation of assured deletion.Theoretical analysis and experimental results show that the proposed approach can meet the assured deletion requirements of user data in cloud storage, and its anonymity can effectively prevent attackers from tracking and analyzing user behavior.